Penyusunan Prosedur Operasi Standar Penghimpunan Dan Penyaluran Dana Unit Simpan Pinjam Koperasi Jasa Kelistrikan Bali - Dwi Ratnadi, Ni Made; Ulupui, I Gusti Ketut Agung; Badera, I Dewa Nyoman; Sujana, I Ketut; Widanaputra, AAGP (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The purpose of this public service was conducted a standard operating procedure (SOP) for Kojalisba cooperative acceptance and distribution of funds. The benefits of activities devoted to the preparation of gathering together and channelling of funds for Kojalisba cooperative can improve the quality of service. In addition it can also increase transparency as well as accountability. The activities of the community services in the Kojalisba Cooperative are producing two books namely SOP for channeling funds and SOP for gathering the funds. Keyword: standard operating procedure for receiving funds, the Fund's channelling standard operating procedures, cooperative